Efecto comparativo del método de fractura mecánica y el método de corte en la viabilidad de las células de la pulpa dental humana de las 24 horas postexodoncia - Flores-Cóndor, Xiomara (2019)
ABSTRACT Aim: In biomaterials and tissue engineering studies, dental pulp cells are used to regenerate or replace deficiencies of bone tissue in the oral cavity. To evaluate its clinical potential, cell culture models are employed, in which different extraction methods of the dental pulp are applied. Mainly, the tooth is broken by fracture mechanics and the cutting method to obtain the dental pulp. However, it is not clear yet which method is the most convenient. Therefore, the purpose of this study was to compare the effect of two methods of fracture mechanical and cutting methods on the dental pulp cell viability. Methodology: Dental pulp tissue was removed of fully developed and healthy teeth of 32 patients between 18 to 40 years, through two techniques: the methods of fracture mechanics (group 1) and cutting (group 2). To determine the cell viability, trypan blue dye was used. The cells were counted in the microscope, blue stained cells (dead) and birefringent (living). Results: Using the mechanical fracture method, 87.72 % of cell viability was obtained. While with the cutting method was achieved a lower viability 83.59 %. There was a significant difference (p = 0.006) when analyzing the data (n = 16 per group) under t-Student test. Conclusions: The use of mechanical fracture method for the extraction of the dental pulp tissue allows to obtain higher percentages of cell viability compared to cutting method.